Интегрированная интеллектуальная система дистанционного обучения - Тимофеев, В. А.; Тулупов, В. В. (УАДО, 2002)
The general principles of the creation of integral intellectuel System of distance tutoring is considered. The modules has included in mathematical maintenance and the structures of operator’s and tutor’s interfaces is described.
Keywords: система дистанционного обучения; образование